The Importance of Effective Communication in Improving the Quality of Classroom Learning Interactions between Teachers and Students - Dwi Suci Rahma Putri; Ahmad Ilham Fadli; Dimas Raba Pramodana; Figo Rangga Bagaskara; Siti Zulaikhah; Imam Syafe’i (Bulletin of Pedagogical Research, 2025)
This study aims to identify effective communication strategies for enhancing student engagement in collaborative learning. Collaborative learning is an educational approach that emphasizes interaction among students to achieve shared academic goals. However, student engagement in this model is often influenced by various factors, particularly the communication methods employed by educators. This research analyzes a range of communication strategies that promote active student participation, including verbal and non-verbal communication, as well as the use of digital technologies that support group interaction. A qualitative research method was adopted, using case studies from several schools that implement collaborative learning. The findings indicate that transparent and inclusive communication, combined with constructive feedback, significantly boosts student motivation and engagement. Furthermore, the integration of technology as a communication support tool has been shown to enhance student interaction and facilitate collaboration in completing group tasks. This study contributes to the development of more effective communication approaches for collaboration-based instruction by deepening the understanding of learning concepts, refining communication strategies, and fostering an inclusive and interactive classroom environment.